Resistance of Pseudomonas aeruginosa to multiple Î²-lactam antibiotics - Hassan Abdul Amir, Venus (Al-Qadisiyah Journal of Pure Science, 2018)
A total of 90 Pseudomonas aeruginosa (P.aeruginosa) strains clinical samples were collected from burn, ear, and foot diabetic samples in Al-Hilla, and Marjan teaching hospitals were identified to species level with a VITEK-2 system. The susceptibility to 11 antibiotics were tested using disc diffusion test resulting in 55.4% of 90 P.aeruginosa isolates were resistant to 11 antibiotics. Cefinase discs impregnated with nitrocefin method was used for the detection of Î²-lactamase production in antibiotics resistant 90 P.aeruginosa isolates. Results showed that 56% isolates were able to produce Î²-lactamase.